Census of Population and Housing, 1990 (United States): Summary Tape File 3C ([Verlag nicht ermittelbar], 1993)
Summary Tape File 3C contains summaries for the entire United States. The collection provides sample data weighted to represent the total population and also contains 100-percent counts and unweighted sample counts for total persons and total housing units. Additional population and housing variables include age, ancestry, disability, citizenship, education, income, marital status, race, sex, travel time to work, rent, tenure, value of housing unit, number of vehicles, and monthly owner costs. The collection provides 178 population tables and 99 housing tables. The geographic hierarchy includes the following levels: United States, region, division, state, county, county subdivision, place with 10,000 or more persons, consolidated city, Alaska Native Regional Corporation, Metropolitan Statistical Area, and Urbanized Area.